Advancing Peripheral Artery Disease Quality of Care and Outcomes Through Patient-Reported Health Status Assessment: A Scientific Statement From the American Heart Association. Issue 20 (13th October 2022) - Smolderen, Kim G.; Alabi, Olamide; Collins, Tracie C.; Dennis, Bernard; Goodney, Philip P.; Mena-Hurtado, Carlos; Spertus, John A.; Decker, Carole; ,
Abstract : Peripheral artery disease (PAD) is chronic in nature, and individualized chronic disease management is a central focus of care. To accommodate this reality, tools to measure the impact and quality of the PAD care delivered are necessary. Patient-reported outcomes (PROs) and instruments to measure them, that is, PRO measures, have been well studied in the research and clinical trial context, but a shift toward integrating them into clinical practice has yet to take place. A framework to use PRO measures as indicators of the quality of PAD care delivered, that is, PRO performance measures (PRO-PMs), is provided in this scientific statement. Measurement goals to consider by PAD clinical phenotypes are provided, as well as an overview of potential benefits of adopting PRO-PMs in the clinical practice of PAD care, including reducing unwanted variability and promoting health equity. A central discussion with considerations for risk adjustment of PRO-PMs, individualized PAD care, and the need for patient engagement strategies is offered. Furthermore, necessary conditions in terms of required competencies and training to handle PRO-PM data are discussed because the interpretation and handling of these data come with great responsibility and consequences for designing care that adopts a broader framework of risk that goes beyond the inclusion of biomedical variables. To conclude, health system perspectives and an agenda to reach the next steps in the implementation of PRO-PMs in PAD care are offered.